Media, 9/11, and fear: a national survey of Australian community responses to images of terror - Balnaves, Mark; Aly, Anne (University of Queensland, 2007)
The history, politics, and psychology of fear have had extensive press since the attack on the World Trade Center in New York by AI-Qaeda terrorists. Fear of any kind, as Robin (2002) points out, has the potential to reinforce unequal power relations. Identifying and exposing fear and its consequences, empirically as well as politically, is essential to the democratic state, just as exposing bullies is essential to a safe schooling environment. Interestingly, however, there have been few measures of fear, for policy purposes, and explorations into exactly how afraid communities might have become after 9/7 7. In this paper, the authors report on a national survey of fear in Australia and how communities have reacted to terrorism messages.